Making resource adequacy a private good: the good, the bad, and the ugly - Ren, X; Savelli, I; Morstyn, T (Cell Press, 2024)
Xiyu Ren is a DPhil candidate at the Smith School of Enterprise and the Environment, the School of Geography and the Environment, and the Institute for New Economic Thinking at the Oxford Martin School of the University of Oxford. Her research interests lie in energy and environmental economics, particularly in energy modeling, electricity market design, times-series analysis, and environmental policies. Iacopo Savelli is a postdoctoral researcher in applied economics at the GREEN Centre, Bocconi University. He is the PI of the peer-reviewed project “Decarbonising the energy system by incentivising energy storage in the right places,” investigating the role of grid-scale energy storage in decarbonizing the energy system. Previously, he was a postdoc at the University of Edinburgh and the University of Oxford working on energy market design. He holds a PhD in engineering, an MS in finance, and a BS in economics. He taught selected energy economics topics at the University of Oxford and the University of Siena. Thomas Morstyn is associate professor in power systems with the Department of Engineering Science of the University of Oxford, where he leads a research group focused on power system control and energy market design. He is also a tutorial fellow at Hertford College and an honorary fellow at the University of Edinburgh. He is an associate editor of IEEE Transactions on Power Systems and co-chairs the IEEE Power & Energy Society Taskforce on Quantum Computing for Power System Operations. His research focuses on the design of control systems and markets to enable the large-scale integration of distributed power system flexibility.